2014
DOI: 10.1002/imhj.21438
|View full text |Cite
|
Sign up to set email alerts
|

The Eye of the Begetter: Predicting Infant Attachment Disorganization From Women's Prenatal Interpretations of Infant Facial Expressions

Abstract: Infant-caregiver attachment disorganization has been linked to many long-term negative psychosocial outcomes. While various prevention programs appear to be effective in preventing disorganized attachment, methods currently used to identify those at risk are unfortunately either overly general or impractical. The current investigation tested whether women's prenatal biases in identifying infant expressions of emotion--tendencies previously shown to relate to some of the maternal variables associated with infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…Two papers were drawn from the study mentioned earlier in relation to depression (Hughes et al, ; Turton et al, ), with similar limitations regarding the low percentage of participants meeting diagnostic criteria for PTSD (only assessed in relation to prior stillbirth: 23% antenatal and 5.8% postnatal). The level of self‐reported trauma symptomology in the Bernstein et al () sample was also low, with dissociation scores in the Schuengel et al () sample only mildly above the normal range. In contrast, Bosquet Enlow et al () found that elevated maternal self‐reported PTSD symptoms were predictive of an increased likelihood of disorganised attachment, b = 2.58, p = .005, OR = 13.17, 95% CI [2.19, 79.13], in a sample with moderate levels of symptomology.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Two papers were drawn from the study mentioned earlier in relation to depression (Hughes et al, ; Turton et al, ), with similar limitations regarding the low percentage of participants meeting diagnostic criteria for PTSD (only assessed in relation to prior stillbirth: 23% antenatal and 5.8% postnatal). The level of self‐reported trauma symptomology in the Bernstein et al () sample was also low, with dissociation scores in the Schuengel et al () sample only mildly above the normal range. In contrast, Bosquet Enlow et al () found that elevated maternal self‐reported PTSD symptoms were predictive of an increased likelihood of disorganised attachment, b = 2.58, p = .005, OR = 13.17, 95% CI [2.19, 79.13], in a sample with moderate levels of symptomology.…”
Section: Resultsmentioning
confidence: 80%
“…Of the remaining eight studies, the authors of only one study reported a significant association with disorganised attachment (Hayes et al, 2013). However, five of the eight studies did not have a primary focus on the impact of maternal depression on attachment (Bernstein et al, 2014;Emery et al, 2008;Hughes et al, 2001;Hughes et al, 2006;Leerkes et al, 2017). The severity of symptoms in these samples were low or unreported, including Hughes et al (2006) which was given a moderate severity rating in relation to trauma symptoms.…”
Section: Antenatal Depressionmentioning
confidence: 99%
“…The findings with regards to the impact of PTSD in interpreting infant emotion also have important implications. These results suggest that biases for women with PTSD are different to those observed in anxiety and depression, but also may be dependent on the trauma type or characteristics (Bernstein et al, 2014;Kne?eviá & Jovan?evi?, 2004). The results suggest that mother's may be more biased towards perceiving certain emotional expressions which may then play out when a mother is interacting with her infant, again leading to less sensitivity towards her infants needs.…”
Section: Discussionmentioning
confidence: 89%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. (e.g., anxious, angry;van Honk et al, 2001), lack of knowledge about normative infant development (e.g., describing an infant as intentionally devious or seductive; Butterfield, 1993), and negative experiences and expectations within interpersonal relationships based on prior relationship difficulties (e.g., intimate partner aggression; R. E. Bernstein, Tenedios, Laurent, Measelle, & Ablow, 2014;de Castro, 2007). With regard to psychosocial parenting risk, no studies to date have examined the influence of mothers' own histories of child maltreatment and negative intimate partner experiences on their perceptions of infant emotions in relation to their actual parenting behaviors with their infants.…”
Section: Parental Perceptions Of Infant Emotion and Associations Withmentioning
confidence: 99%